Multiple Roles of Isocyanides in Palladium‐Catalyzed Imidoylative Couplings: A Mechanistic Study. Issue 43 (8th September 2016) - Perego, Luca A.; Fleurat‐Lessard, Paul; El Kaïm, Laurent; Ciofini, Ilaria; Grimaud, Laurence
Abstract: Kinetic, spectroscopic and computational studies examining a palladium‐catalyzed imidoylative coupling highlight the dual role of isocyanides as both substrates and ligands for this class of transformations. The synthesis of secondary amides from aryl halides and water is presented as a case study. The kinetics of the oxidative addition of ArI with RNC‐ligated Pd 0 species have been studied and the resulting imidoyl complex [(ArC=NR)Pd(CNR)2 I] (Ar=4‐F‐C6 H4, R= t Bu) has been isolated and characterized by X‐ray diffraction. The unprecedented ability of this RNC‐ligated imidoyl‐Pd complex to undergo reductive elimination at room temperature to give the amide in the presence of water and an F − /HF buffer is demonstrated. Its behavior in solution has also been characterized, revealing an unexpected strong tendency to give cationic complexes, and notably [(ArC=NR)Pd(CNR)3 ] + with excess isocyanide and [(ArC=NR)Pd( P P ^ )(CNR)] + with bidentate phosphines ( P P ^ ). These species may be responsible for catalyst deactivation and side‐reactions. Ab initio calculations performed at the DFT level allowed us to rationalize the multiple roles of RNC in the different steps of the catalytic cycle. Abstract : Double duty : Isocyanides are substrates and ligands at the same time in Pd‐catalyzed imidoylative couplings. A detailed mechanistic study of the amidation of aryl halides explains how the substrate tunes the reactivity of intermediates by forming unexpected cationic resting states, and rationalizes the proper choice of the base in these couplings (see scheme).